Research priorities to reduce the global burden of dementia by 2025. Issue 12 (November 2016) - Shah, Hiral; Albanese, Emiliano; Duggan, Cynthia; Rudan, Igor; Langa, Kenneth M; Carrillo, Maria C; Chan, Kit Yee; Joanette, Yves; Prince, Martin; Rossor, Martin; Saxena, Shekhar; Snyder, Heather M; et al.
Summary: At the First WHO Ministerial Conference on Global Action Against Dementia in March, 2015, 160 delegates, including representatives from 80 WHO Member States and four UN agencies, agreed on a call for action to reduce the global burden of dementia by fostering a collective effort to advance research. To drive this effort, we completed a globally representative research prioritisation exercise using an adapted version of the Child Health and Nutrition Research Initiative method. We elicited 863 research questions from 201 participants and consolidated these questions into 59 thematic research avenues, which were scored anonymously by 162 researchers and stakeholders from 39 countries according to five criteria. Six of the top ten research priorities were focused on prevention, identification, and reduction of dementia risk, and on delivery and quality of care for people with dementia and their carers. Other priorities related to diagnosis, biomarkers, treatment development, basic research into disease mechanisms, and public awareness and understanding of dementia. Research priorities identified by this systematic international process should be mapped onto the global dementia research landscape to identify crucial gaps and inform and motivate policy makers, funders, and researchers to support and conduct research to reduce the global burden of dementia. Efforts are needed by all stakeholders, including WHO, WHO Member States, and civil society, to continuously monitor research investments and progress, through international platforms such as a Global Dementia Observatory. With established research priorities, an opportunity now exists to translate the call for action into a global dementia action plan to reduce the global burden of dementia.